2016
DOI: 10.1007/s00216-016-9871-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of the degradation of a multidrug transporter using a non-radioactive pulse chase method

Abstract: Proteins are constantly synthesized and degraded in living cells during their growth and division, often in response to metabolic and environmental conditions. The synthesis and breakdown of proteins under different conditions reveal information about their mechanism of function. The metabolic incorporation of non-natural amino acid azidohomoalanine (AHA) and subsequent labeling via click chemistry emerged as a non-radioactive strategy useful in the determination of protein kinetics and turnover. We used the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Taken together, the low accumulation and similar rate of efflux of EtBr across time in SL1344 suggests that although acrAB transcription peaks in mid-exponential phase, activity of the assembled AcrAB-TolC complex remains constant. The AcrB protein is known to be very stable once made, with a predicted half-life of 6 days ( 26 ). To measure AcrB protein level at different points during growth, a strain was constructed in which the AcrB protein was tagged with GFP at the C terminus as previously described ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the low accumulation and similar rate of efflux of EtBr across time in SL1344 suggests that although acrAB transcription peaks in mid-exponential phase, activity of the assembled AcrAB-TolC complex remains constant. The AcrB protein is known to be very stable once made, with a predicted half-life of 6 days ( 26 ). To measure AcrB protein level at different points during growth, a strain was constructed in which the AcrB protein was tagged with GFP at the C terminus as previously described ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Active degradation should be negligible compared to the timescale of the search process. The majority of proteins in E. coli are not subject to rapid degradation [ 46 ] and individual membrane proteins that have been studied in detail displayed life-times as long as 6 days [ 47 ]. Spontaneous separation of CadC dimers from the membrane (or proteolytic cleavage) also do not appear to play a role, since CadC is deactivated by external cadaverine [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in E. coli it has also been observed that AcrA and AcrB lasted for approximately six days (Chai et al. 2016 ).…”
Section: Model Formulationmentioning
confidence: 96%